2004
DOI: 10.1136/jcp.2004.018846
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of extensive necrosis in renal cell carcinoma

Abstract: Aims: Evidence suggests that the presence of tumour necrosis is an adverse prognostic factor in renal cell carcinoma (RCC). However, it has also been shown that tumour regression, a microscopic feature associated with necrosis, may be a favourable short term prognostic factor in RCC. Methods: Pathology reports of 253 RCCs from 1992 to 2001 were reviewed, and identified 37 tumours with substantial macroscopic or microscopic necrosis. Microscopic pathology, TNM 1997 tumour stage, and clinical follow up were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
(13 reference statements)
0
13
0
1
Order By: Relevance
“…Due to the limited number of tumours, it was impossible to draw any conclusions concerning the potential prognostic information of necrosis. An inadequate blood sup-ply is probably the most likely reason for tumour necrosis, but there are also other plausible mechanisms such as immune reactions [31] . In the present study no evaluation of necrosis was performed; actually, with the limited material assessed by TMA we tried to avoid necrotic parts of the tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the limited number of tumours, it was impossible to draw any conclusions concerning the potential prognostic information of necrosis. An inadequate blood sup-ply is probably the most likely reason for tumour necrosis, but there are also other plausible mechanisms such as immune reactions [31] . In the present study no evaluation of necrosis was performed; actually, with the limited material assessed by TMA we tried to avoid necrotic parts of the tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they identified Ki67 expression as a surrogate marker for necrosis. Foria et al [31] assessed patients with RCC and found that tumours with extensive necrosis were rare. Due to the limited number of tumours, it was impossible to draw any conclusions concerning the potential prognostic information of necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These terms are unfortunate, as it is not coagulative necrosis. Further, while thrombo‐embolic coagulative necrosis is usually macroscopic and may be extensive, tumour‐related necrosis may be macroscopic or microscopic . The aetiology of this form of necrosis is unknown, although an immune reaction or microvascular changes have been postulated .…”
Section: Future Developmentsmentioning
confidence: 99%
“…Sarkomatoid ve rabdoid diferansiasyon gösteren tümörlerde rekürrens ve metastaz oranının fazla olduğu ve bu tümörlerde orijinal tümör tipinin de raporda belirtilmesi gerektiği vurgulanmıştır. Son çalışmalar RHK'larda koagülatif tümör nekrozunun prognostik önemi olduğunu ortaya koymaktadır (34,35). Makroskopik ve mikroskopik tümör nekrozunun ve nekroz oranının raporlarda yer alması gerektiği konusunda da görüş birliği sağlanmıştır.…”
Section: Uluslararası üRolojik Patoloji Derneği Derecelendirme Sistemunclassified